Respectus Philologicus, 2009 Nr. 16 (21) - Bankauskaitė, Gabija (Respectus Philologicus, 2009)
CONTENTSI. PROBLEMS AND SOLUTIONSDanguolė Melnikienė (Lithuania). The Issue of the Addressee in Receptive and Productive Dictionaries...11Eleonora Lassan (Lithuania). The Time of Losers...21Yelena G. Zadvornaya (Belarus). Russian Litanies: Types and Characteristics of the Genre...35Evgeny E. Anikin (France). The 2008 US Presidential Election in the Mirror of Sports Metaphor (in the French Press)...46II. FACTS AND REFLECTIONSZinaida D. Popova (Russia). The Ways of Representation of Concepts as a Problem of Cognitive Linguistics... 56Marzena Marczewska (Poland). The Willow Tree in the Medical Folk Rituals...62Natalia Solovyova (Belarus). The Concepts of “War” and “Peace” in the Old Russian Language Picture of the World: The Genesis of Antonymous Relations...73Olga N. Charykova (Russia). National Specificity of Metaphorical Conceptualization of the World...82Dalia Eigirdienė (Lithuania). On the Peculiarities of the Worldview Reflected In Lithuanian and Russian Zoonymic Phraseology...90Aleksandras Krasnovas (Lithuania). Reception Theory and Practice of Reading...96Asija Kovtun (Lithuania). Parallels Between Deconstructionist and Creator – Paul de Man and Czeslaw Milosz...104Lidia Mazur-Mierzwa (Poland). Wislawa Szymborska in Russian Translation...116Jolanta Chwastyk-Kowalczyk (Poland). Memoirs of Lwów Citizens in Exile Published after the World War II...126Gabija Bankauskaitė-Sereikienė, Žydrė Dargužytė (Lithuania). Rainer Maria Rilke’s Ideas in Father Stanislovas’ Sermons...137Tatsiana V. Eromeitchik (Belarus). The Evaluative Focus of Social Advertising in Belarus...150Laima Kalėdienė (Lithuania). The Statistical Approach to Vernacularisms in The Dictionary Of Modern Lithuanian Language...159Asta Kazlauskienė, Gailius Raškinis (Lithuania). Phone Frequency in Standard Lithuanian...169III. OPINIONAlgis Braun (Lithuania). Lithuanian Grammar, English Words: Cross-Linguistic Influence and Students’ Written Errors...183IV. OUR TRANSLATIONSPatrick Seriot (Switzerland). Oxymoran or Misundersanding. Anna Wierzbicka’s Universal Relativism of Natural Semantic Metalanguage. Translated by Vilhelmina Vitkauskienė...193V. SCIENTIFIC LIFE CHRONICLEConferences , eventsEleonora Lassan (Lithuania). Once Upon a Time in Ekaterinburg…203Books reviewsPavel Lavrinec (Lithuania). БРИО, Валентина, 2008. Поэзия и поэтика города: Wilno – הנליו – Vilnius...205Kazimierz Luciński (Poland). Bulat Okudzhava’s memory will live on for ever in Poland. MAZUR-MERZWA, Lidia, 2008. Булат Окуджава в польских переводах. Когнитивные стратегии польского переводоведения...209Ina Kažuro (Lithuania). ЛАССАН, Элеонора, 2008. Лингвокультурология. Очерк русской концептологии...213Wiesław Caban (Lenkija / Polska). ILGIEWICZ, Henryka, 2008. Societates Academicae Vilnenses. Towarzystwo Przyjaciół Nauk w Wilnie (1907-1939) i jego poprzednicy...216Vilnius University Kaunas Faculty of Humanities: journal of scientific lifeDaiva Aliūkaitė (Lithuania). Emotions suppressed by language: Joviality without a smile...220Skirmantė Biržietienė, Saulutė Juzelėnienė (Lithuania). Linguistics, Literature Studies and advertising or tracing back to the ideas of young linguists of VU KHF...222Announce...224VI. REQUIREMENTS FOR PUBLICATION...226VII. OUR AUTHORS... 234
Keywords: none